2017
DOI: 10.1111/aogs.13152
|View full text |Cite
|
Sign up to set email alerts
|

Does surgery for deep infiltrating bowel endometriosis improve fertility? A systematic review

Abstract: Introduction. Reduced fertility is a major concern in women with endometriosis. The influence of surgery of deep infiltrating endometriosis (DIE) affecting the bowel wall on fertility is controversial and the literature on this field is heterogeneous. In this review we addressed whether surgery for bowel DIE improves the spontaneous pregnancy rate, and the results of in vitro fertilization (IVF), and the potential risk of such surgery. Material and methods. We conducted a literature search including the terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 28 publications
1
57
0
4
Order By: Relevance
“…There is increasing but still limited evidence that infertile women with advanced stage DIE do benefit from radical surgery regarding altered postsurgical spontaneous and IVF PRs . However, the situation is complex in this patient group because multiple additional influencing factors such as age, ovarian reserve, and the presence or absence of adenomyosis do influence postoperative fertility outcomes and must be taken into account in the light of the possible severe complications of radical surgery .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing but still limited evidence that infertile women with advanced stage DIE do benefit from radical surgery regarding altered postsurgical spontaneous and IVF PRs . However, the situation is complex in this patient group because multiple additional influencing factors such as age, ovarian reserve, and the presence or absence of adenomyosis do influence postoperative fertility outcomes and must be taken into account in the light of the possible severe complications of radical surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Deep infiltrating endometriosis (DIE) is defined as infiltrative growth of extrauterine endometrial glands and stroma extending below the peritoneal surface >5 mm . DIE affecting the colon and/or rectum has been associated with severe pain symptoms, altered digestive function, and decreased fertility, consequently leading to impaired quality of life in these patients. Medical treatment does offer a valuable therapeutic option in the majority of women affected with colorectal DIE .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several investigators observed substantial improvements of bowel symptoms during hormonal treatment (10)(11)(12)(13)(14). Disentangling the uncertainties of the role of medical therapy in women with infiltrating bowel endometriosis seems exceedingly important, as excisional procedures with opening of the bowel lumen are generally effective in relieving intestinal symptoms but are also associated with severe short-and long-term complications in about one of 10 patients (for example, intestinal leakage, anastomosis dehiscence, septic peritonitis, rectovaginal fistula formation, bowel anastomosis stenosis, iatrogenic neurologic bladder dysfunction with need for long periods of selfcatheterization, and postoperative constipation and de novo rectal dysfunction) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The incidence of some complications is associated also with the distance between the lower margin of resection and the anal verge (9,26).…”
Section: Introductionmentioning
confidence: 99%